Implementation of Visual, Auditory, and Kinesthetic (VAK) Differentiated Learning to Improve Scientific Communication Skill in Science Subjects - Fitra, Devi Kurnia; Copriady, Jimmi; Zulirfan, Zulirfan (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2025)
This study aims to improve students' scientific communication skills through the implementation of differentiated VAK (Visual, Auditory, and Kinesthetic) learning in the